Driving and Back Pain among Online Motorcyclist Transportation in Jakarta - Tanjung, Julia Rahadian; Tan, Wanda Permata Prihastanti; Santosa, Mariani (School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia, 2024)
Introduction: Low Back Pain (LBP) is a musculoskeletal disorder in the form of pain in the lower back caused by various factors. One of the common factors is work. Work factors that can cause LBP are body position, posture, workplace design, repetition, duration of work, and work that forces labor. One of the risky jobs is being an online motorbike taxi driver (“Ojek”), one of Jakarta's most popular transportation types. By using an application to call, an online “Ojek” not only acts as a means of transporting people or goods but can also be used to buy goods and order food. The prolonged sitting position in static conditions and limited space to move around contribute to LBP in “Ojek” drivers. This study investigates the association between driving duration and LBP in “Ojek” drivers. Methods: This was an observational analytic study with a cross-sectional approach on 63 male online “Ojek” drivers aged 25-35 with normal BMI who met the inclusion and exclusion criteria. The study was conducted in the Central Jakarta area in November-December 2019. The sampling technique is accidental sampling. Duration of the driving questionnaire and Nordic Low Back Pain Questionnaire were used to gather the data. A bivariate analysis test was conducted with a chi-square statistical test with p ≤ 0,05. Results: Thirty-eight online ‘Ojek” drivers (60.32%) reported having LBP in the last 12 months. Bivariate analysis by chi-square statistical test found that the p-value equals 0.414 between driving duration and incidence. Conclusion: Driving duration is unrelated to the incidence of lower back pain. LBP is most common in drivers driving more than 8 hours daily. Keywords: driving duration - online drivers - low back pain - prolonged sitting - static condition